Referral strategy for early recognition of axial spondyloarthritis: consensus recommendations from the Hong Kong Society of Rheumatology. (26th October 2013) - Mok, C. C.; Tam, L. S.; Leung, M. H.; Ying, K. Y.; To, C. H.; Lee, K. L.; Ho, L. Y.; Yip, M. L.; Tsui, H. S.; Chan, T. H.; Lee, K. W.; Li, E. K. M.; et al.
Abstract: Low back pain is one of commonest problems prompting a visit to the family physician. Up to 5% of patients with chronic low back pain in the primary care setting are diagnosed as having spondyloarthritis, which includes the prototype disease ankylosing spondylitis. Making a diagnosis of ankylosing spondylitis is often delayed for years, leading to significant pain, impairment of quality of life, disability and productivity loss. A recent breakthrough in the treatment of spondyloarthritis is the anti‐tumor necrosis factor‐alpha biologics, which lead to rapid relief of pain and inflammation, and improvement in all clinical parameters of the disease. Patients with early spondyloarthritis often respond better than those with late established disease. With proper recognition of inflammatory back pain, and the use of magnetic resonance imaging, spondyloarthritis can now be diagnosed much earlier before features are evident on plain radiographs. Referral to the rheumatologist based on onset of back pain (> 3 months) before the age of 45 years, and an inflammatory nature of the pain, or the presence of human leukocyte antigen‐B27, or sacroiliitis by imaging, have been confirmed in multi‐center international studies to be a pragmatic approach to enable early diagnosis of spondyloarthritis. This referral strategy has recently been adopted by the Hong Kong Society of Rheumatology for primary care physicians and non‐rheumatology specialists.